The maize ZmMIEL1 E3 ligase and ZmMYB83 transcription factor proteins interact and regulate the hypersensitive defence response. (6th April 2021) - Karre, Shailesh; Kim, Saet‐Byul; Samira, Rozalynne; Balint‐Kurti, Peter
Abstract: The plant hypersensitive response (HR), a rapid cell death at the point of pathogenesis, is mediated by nucleotide‐binding site, leucine‐rich repeat (NLR) resistance proteins (R‐proteins) that recognize the presence of specific pathogen‐derived proteins. Rp1‐D21 is an autoactive maize NLR R‐protein that triggers HR spontaneously. We previously mapped loci associated with variation in the strength of HR induced by Rp1‐D21. Here we identify the E3 ligase ZmMIEL1 as the causal gene at a chromosome 10 modifier locus. Transient ZmMIEL1 expression in Nicotiana benthamiana reduced HR induced by Rp1‐D21, while suppression of ZmMIEL1 expression in maize carrying Rp1‐D21 increased HR. ZmMIEL1 also suppressed HR induced by another autoactive NLR, the Arabidopsis R‐protein RPM1D505V, in N. benthamiana . We demonstrated that ZmMIEL1 is a functional E3 ligase and that the effect of ZmMIEL1 was dependent on the proteasome but also that levels of Rp1‐D21 and RPM1D505V were not reduced when coexpressed with ZmMIEL1 in the N. benthamiana system. By comparison to a similar system in Arabidopsis, we identify ZmMYB83 as a potential target of ZmMIEL1. Suppression of ZmMYB83 expression in maize lines carrying Rp1‐D21 suppressed HR. Suppression of ZmMIEL1 expression caused an increase in ZmMYB83 transcript and protein levels in N. benthamiana and maize. Using coimmunoprecipitation and bimolecular fluorescence complementation assays, we demonstrated that ZmMIEL1 and ZmMYB83 physically interacted. Additionally, ZmMYB83 and ZmMIEL1 regulated the expression of a set of maize very long chain fatty acid (VLCFA) biosynthetic genes that may be involved in regulating HR. Abstract : We present evidence that induction of the hypersensitive defence response by the maize Rp1‐D21 resistance protein requires the ZmMYB83 transcription factor, which is targeted for degradation by the ZmMIEL1 E3 ligase protein.